MENGKAJI EFEKTIVITAS MAGANG KEARSIPAN DALAM PENGEMBANGAN KOMPETENSI PROFESIONAL ASSESSING THE EFFECTIVENESS OF ARCHIVAL INTERNSHIPS IN DEVELOPING PROFESSIONAL COMPETENCIES - Setyawan, Herman; Santosa, Heri; Putri, Adhitya Eka (Jurnal Kearsipan, 2024)
Abstract An archival internship is a structured educational program or work experience that aims to equip students or professionals early in their careers in the archival field. Archival internships aim to provide provisions and develop professional competence in archives. This research aims to examine the effectiveness of archival internships in the professional development of pupils, students, and graduates of various study programs in Indonesia. This research uses quantitative methods by proposing hypotheses based on conceptual models. Data was obtained from 84 respondents who are currently or have participated in archival internships at various government, and private institutions, as well as colleges or universities. The collected data was then analyzed using PLS-SEM. The research results show that various factors influence the effectiveness of archival internships, namely internship experience, supervisory support, skills development, and perceived career readiness. All factors have a positive effect on the effectiveness of archival internships, although some of them are not significant. Keywords: internship effectiveness; professional competence; archival internship Abstrak Magang kearsipan adalah program pendidikan terstruktur atau pengalaman kerja yang bertujuan untuk membekali mahasiswa atau profesional awal karier dalam bidang kearsipan. Magang kearsipan bertujuan untuk memberikan bekal dan mengembangkan kompetensi profesional di bidang kearsipan. Tujuan penelitian ini adalah untuk mengkaji efektivitas magang kearsipan dalam pengembangan profesional siswa, mahasiswa, dan lulusan berbagai program studi di Indonesia. Penelitian ini menggunakan metode kuantitatif dengan mengajukan hipotesis berdasarkan model konseptual. Data diperoleh dari 84 responden yang sedang atau pernah mengikuti magang kearsipan di berbagai institusi pemerintah, swasta, maupun perguruan tinggi atau universitas. Data yang terkumpul kemudian dianalisis dengan PLS-SEM. Hasil penelitian menunjukkan bahwa terdapat berbagai faktor yang mempengaruhi efektivitas magang kearsipan yaitu pengalaman magang, dukungan pengawasan, pengembangan keterampilan, dan kesiapan karier yang dirasakan. Semua faktor berpengaruh positif terhadap efektivitas magang kearsipan, meskipun beberapa di antaranya tidak signifikan. Kata kunci: efektivitas magang; kompetensi profesional; magang kearsipan